A detailed study on the damage evolution and failure assessment of single-lap hybrid joints in CFRP laminates under tensile loading. (1st November 2022) - Paliwal, Isha; Ramji, M.
Abstract: Hybrid joints have potential to improve the joint strength and efficiency compared to the bonded or bolted joint. Several studies have been performed to understand the influence of various design parameters on the hybrid joint strength. However, very few studies have been reported on the complex failure mechanism of the hybrid joint. In this study, a detailed analysis is carried out to understand the failure mechanism of the hybrid joint in Carbon fiber reinforced plastic (CFRP) laminate having [ 0 / + 45 / 90 / − 45 ] s layup sequence under tensile loading both experimentally and numerically. Analysis of a simple bonded and bolted joint configurations are also included for comparison purposes. The acoustic emission (AE) technique is utilized for the damage assessment and the 3D digital image correlation (DIC) technique is used to capture the whole field strain around the bolt region. A detailed fractographic study using a digital optical microscope is also carried out to critically ascertain the presence of different damage modes. An in-house instrumented bolt is realized to measure the load transfer through it upon loading. A finite element based progressive damage model (PDM) along with the cohesive element is also developed to predict the damage evolution and failure mechanism for all the joint configurations.